2018
DOI: 10.7717/peerj.4617
|View full text |Cite
|
Sign up to set email alerts
|

Coarse- and fine-scale patterns of distribution and habitat selection places an Amazonian floodplain curassow in double jeopardy

Abstract: Patterns of habitat selection are influenced by local productivity, resource availability, and predation risk. Species have taken millions of years to hone the macro- and micro-habitats they occupy, but these may now overlap with contemporary human threats within natural species ranges. Wattled Curassow (Crax globulosa), an endemic galliform species of the western Amazon, is threatened by both hunting and habitat loss, and is restricted to white-water floodplain forests of major Amazonian rivers. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…To study C. globulosa diet, direct observations were carried out in the field during August 2014 to October 2015. Observations occurred while monitoring three individuals (two females and one male) captured and tagged with VHF transmitters in September and October 2014 (Leite et al 2018), in addition to other individuals observed casually at the study site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study C. globulosa diet, direct observations were carried out in the field during August 2014 to October 2015. Observations occurred while monitoring three individuals (two females and one male) captured and tagged with VHF transmitters in September and October 2014 (Leite et al 2018), in addition to other individuals observed casually at the study site.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is present in five South American countries, its ecology is little known, with most knowledge based on anecdotal information Communicated by: Marcos P. Dantas (BirdLife International 2016;. In Brazil, where the largest population is assumed to occur, only four studies of the species have been published (Santos 1998;Haugaasen and Peres 2008;Leite et al 2017;Leite et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many wild animals require multiple habitats to obtain various resources (Raynor et al, 2017;Leite et al, 2018), which would provide them opportunities for predation, reproduction, and shelter (Doligez, Danchin & Clobert, 2002;Hyslop, Cooper & Meyers, 2009;O'Hanlon, Herberstein & Holwell, 2015). Effective conservation and management of species depends on an understanding of habitat requirements, particularly if these aspects change seasonally.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially the case for species susceptible to habitat loss or fragmentation (Willems & Hill, 2009;Ali et al, 2017;Mandlate, Cuamba & Rodrigues, 2019). However, information related to habitat requirements is often scarce when a species has low population densities, narrow and remote habitat, receives little low public attention, and when venomous animals can endanger investigators (Rechetelo et al, 2016;Sutton et al, 2017;Leite et al, 2018). Through investigations into the habitat features associated with a species detection, the important variables that influence habitat association patterns can be found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation